2014
DOI: 10.1007/s13277-014-2626-1
|View full text |Cite
|
Sign up to set email alerts
|

The expression profiles of microRNAs in Kaposi’s sarcoma

Abstract: Kaposi's sarcoma (KS) is a multicentric angioproliferative tumor of mesenchymal origin. The molecular and biologic aspects of KS are not fully understood. MicroRNAs are non-protein-coding small RNAs in the size range 19-25 nucleotides (nt) that play important roles in biological processes, including cellular differentiation, proliferation, and death. We performed a miRNA microarray analysis by detecting six paired KS and matched adjacent healthy tissues using the 7th generation of miRCURY(TM) LNA Array (v.18.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…Due to the high expression levels of miR-K3 in KS lesions [41] and the crucial role that the miR-K3/GRK2/CXCR2/AKT axis might play in the KS pathogenesis [40], in this study, we have shown that, by targeting GRK2, miR-K3 not only facilitates KSHV latency, but also mediates KSHV-induced angiogenesis by activating the CXCR2/AKT pathway. These novel findings demonstrate that by targeting the GRK2/CXCR2/AKT pathway through encoding a miRNA, KSHV maintains its latency and induces a pro-angiogenic microenvironment to promote tumorigenesis.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Due to the high expression levels of miR-K3 in KS lesions [41] and the crucial role that the miR-K3/GRK2/CXCR2/AKT axis might play in the KS pathogenesis [40], in this study, we have shown that, by targeting GRK2, miR-K3 not only facilitates KSHV latency, but also mediates KSHV-induced angiogenesis by activating the CXCR2/AKT pathway. These novel findings demonstrate that by targeting the GRK2/CXCR2/AKT pathway through encoding a miRNA, KSHV maintains its latency and induces a pro-angiogenic microenvironment to promote tumorigenesis.…”
Section: Introductionmentioning
confidence: 75%
“…This balance is controlled by RTA and regulated by latent gene products, such as LANA, cellular signaling pathways, and cellular and/or viral miRNAs [52]. As a KSHV-encoded miRNA, miR-K3 is highly expressed in KS tumors [41], and in KSHV-infected PEL cell lines [53, 54], indicating its potential role in viral lifecycle and its oncogenic potential. So far, the validated targets of miR-K3 included NFIB, MYB, C/EBPα, Ets-1 and GRK2 [19, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…The cross talk between these processes promotes a balance between the proliferation and apoptosis. Increasing studies have shown that miRNAs have important roles in cancer processes, including cell proliferation and apoptosis [24]. MiR-224 enhances the growth ability of CRC cells through accelerating the G1-S phase transition.…”
Section: Mir-224 In Cell Proliferation and Apoptosismentioning
confidence: 99%
“…One study showed that miR-143/145 is an upregulated miRNA biomarker and that miR-221/222, miR-155, and the let-7 family are downregulated in KS [11]. Wu et al [12] clearly identified 170 deregulated miRNAs: 69 were upregulated and 101 downregulated when compared between KS and matched adjacent healthy tissues. In particular, miR-126-3p and the 13 KSHV-related miRNAs were upregulated.…”
Section: Introductionmentioning
confidence: 99%